Lithium nickel cobalt aluminate positive electrode material as well as preparation method and application thereof
By preparing the nickel-cobalt lithium sterate positive electrode material, the combination of the cobalt hydroxide composite material coated with graphene quantum dots and the nickel-cobalt hydroxide precursor and lithium and aluminum sources is solved, and the DCR and cycle performance improvement of the high-nickel positive electrode material is solved. Limited problems achieve the effects of low DCR, high capacity and high cycle stability.
Patent Information
- Application Number
- CN202411551587.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The DC internal resistance DCR and cycle performance improvements of existing high-nickel cathode materials are limited.
Using the preparation method of nickel-cobalt lithium aluminate positive electrode material, by mixing cobalt hydroxide with acid solution to form an electrolyte for electrodeposition, a cobalt hydroxide composite material coated with graphene quantum dots is obtained, and a precursor with nickel-cobalt hydroxide The body is mixed with lithium and aluminum sources and calcined and sintered to prepare a nickel-cobalt lithium aluminate positive electrode material with low DCR, high first discharge specific capacity and high cycle stability.
It significantly reduces the DC internal resistance of the positive electrode material, improves the first discharge specific capacity and cycle stability, and overcomes the problems of lithium nickel mixed discharge and layer spacing reduction caused by the nickel-cobalt-aluminum material in the prior art after reducing the cobalt content. .
Smart Images

Figure CN119447237A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a nickel cobalt aluminum oxide lithium positive electrode material and a preparation method and application thereof. Background Art
[0002] The performance of the electrode mainly depends on the positive electrode material. Among them, high-nickel positive electrode material (the molar amount of nickel element accounts for more than 60% of the molar amount of metal elements) is a common positive electrode material for lithium-ion batteries. It has the advantage of high energy density and has attracted much attention.
[0003] Direct Current Resistance (DCR) is a key factor affecting the cycle performance of lithium-ion batteries. Compared with lithium iron phosphate cathode materials, traditional high-nickel cathode materials have higher direct current resistance (DCR) and poorer cycle performance. Currently, researchers mainly improve them through doping or coating with borates, metal oxides, phosphates, and carbon. However, these improvements have limited effect on improving direct current resistance (DCR) and cycle performance. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the existing high-nickel positive electrode materials in terms of DC internal resistance DCR and limited improvement in cycle performance, thereby providing a nickel cobalt aluminum oxide lithium positive electrode material and a preparation method and application thereof.
[0005] The present invention provides a method for preparing a nickel cobalt aluminum lithium cathode material, comprising the following steps:
[0006] 1) placing cobalt hydroxide in an acid solution to form an electrolyte, using a graphite rod as an electrode material for electrodeposition treatment, and after the electrodeposition treatment, separating the solid in the electrolyte to obtain a cobalt hydroxide composite material coated with graphene quantum dots;
[0007] 2) mixing a nickel-cobalt hydroxide precursor with a lithium source and an aluminum source, and calcining the mixture to obtain a calcined product;
[0008] 3) The cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and the sintered product obtained in step 2) are stirred and mixed, and then sintered to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0009] Preferably, the cobalt hydroxide in step 1) is nano cobalt hydroxide;
[0010] The dosage ratio of the cobalt hydroxide to the acid solution is 1:(5-10), in g:mL;
[0011] The acid solution is selected from aqueous sulfuric acid, aqueous nitric acid, and aqueous hydrochloric acid;
[0012] The mass concentration of acid in the acid solution is 10-15%;
[0013] In step 1), cobalt hydroxide is placed in an acid solution and ultrasonically mixed to form an electrolyte, the ultrasonic mixing power is 50-500W, and the ultrasonic mixing time is 30-120min;
[0014] The current density of the electrodeposition treatment is 90-120 mA / cm 2 The temperature of the electrodeposition treatment is 55-65°C, and the time of the electrodeposition treatment is 0.5-2h.
[0015] Optionally, after the step of separating the solids in the electrolyte is completed, the step of washing and / or drying the separated solids is also included;
[0016] Optionally, the drying comprises freeze drying;
[0017] Optionally, the drying is freeze-drying at -5°C to 0°C for 2-5h.
[0018] Preferably, in step 2), the ratio of the total molar amount of nickel and cobalt in the nickel cobalt hydroxide precursor to the molar amount of aluminum in the aluminum source is (0.9-1.3): (0.01-0.03);
[0019] The total molar amount of nickel element, cobalt element and aluminum element in the nickel cobalt hydroxide precursor is recorded as a, and the molar amount of lithium element in the lithium source is recorded as b, and b:a is (0.95-1.2):1;
[0020] The lithium source is selected from at least one of lithium carbonate, lithium hydroxide and lithium acetate;
[0021] The aluminum source is selected from at least one of aluminum oxide and aluminum hydroxide;
[0022] The chemical formula of the nickel cobalt hydroxide precursor is: Ni x Co y (OH)2, and 0.5≤x<1, 0 <y≤0.5,x+y=1。
[0023] Preferably, the nickel cobalt hydroxide precursor in step 2) includes a nickel cobalt hydroxide precursor with a first particle size and a nickel cobalt hydroxide precursor with a second particle size;
[0024] The median particle size D50 of the first particle size nickel cobalt hydroxide precursor is 2-4 μm;
[0025] The median particle size D50 of the second particle size nickel cobalt hydroxide precursor is 13-17 μm;
[0026] The mass ratio of the first particle size nickel cobalt hydroxide precursor to the second particle size nickel cobalt hydroxide precursor is (1-10): (1-10);
[0027] For example, the mass ratio of the first particle size nickel cobalt hydroxide precursor to the second particle size nickel cobalt hydroxide precursor can be selected as 1:9, 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 5:5, 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, or 9:1.
[0028] Optionally, the specific surface area of the nickel cobalt hydroxide precursor is 5-10m 2 / g, tap density is 1-3g / cm 3 .
[0029] Preferably, the mixing in step 2) includes a first stirring and mixing, a second stirring and mixing, and a third stirring and mixing;
[0030] The first stirring and mixing speed is 500-1500r / min, and the stirring and mixing time is 1-5min;
[0031] The second stirring and mixing speed is 1500-3000r / min, and the stirring and mixing time is 1-5min;
[0032] The third stirring and mixing speed is 3000-4000r / min, and the stirring and mixing time is 10-20min.
[0033] Optionally, no waiting time is set between the first stirring and mixing, the second stirring and mixing, and the third stirring and mixing.
[0034] The calcination in step 2) includes heating to 400-600°C for calcination for 3-5h, then heating to 700-750°C for calcination for 9-12h, and then calcining at 450-550°C for 2-5h;
[0035] Optionally, the heating rate is 1-5°C / min;
[0036] Optionally, the calcination in step 2) includes heating to 400-600°C at a heating rate of 1-5°C / min and calcining for 3-5h, then heating to 700-750°C at a heating rate of 1-5°C / min and calcining for 9-12h, and then calcining at 450-550°C for 2-5h;
[0037] The calcining atmosphere includes an oxygen-containing atmosphere;
[0038] Optionally, the calcination atmosphere includes an air atmosphere or an oxygen atmosphere.
[0039] Optionally, the flow rate of the calcining atmosphere is 1-5 L / min;
[0040] Optionally, after the calcination step, the steps of cooling, crushing and screening are also included.
[0041] Preferably, in step 3), the mass ratio of the cobalt hydroxide composite material coated with graphene quantum dots to the sintered product is (4-5.8):500;
[0042] The stirring and mixing in step 3) includes: first stirring and mixing at a speed of 800-1200 r / min for 1-3 min, then stirring and mixing at a speed of 1800-2200 r / min for 2-5 min, and then stirring and mixing at a speed of 3200-3600 r / min for 10-18 min.
[0043] Optionally, no waiting time is set during variable speed stirring and mixing.
[0044] Preferably, the sintering temperature in step 3) is 570-630° C., and the sintering time is 5-7 h;
[0045] The sintering atmosphere includes an oxygen-containing atmosphere;
[0046] Optionally, the sintering atmosphere includes an air atmosphere or an oxygen atmosphere.
[0047] Optionally, the heating rate of the sintering is 1-5°C / min.
[0048] Optionally, a cooling step is also included after the sintering step.
[0049] Preferably, the step of mixing the nickel cobalt hydroxide precursor with the lithium source and the aluminum source in step 2) further comprises the step of adding a doping metal source;
[0050] Optionally, in step 2), a nickel cobalt hydroxide precursor is mixed with a lithium source, an aluminum source and a doping metal source;
[0051] Optionally, the doping metal source in step 2) is selected from at least one of zinc oxide, magnesium oxide, aluminum oxide, chromium oxide, strontium oxide, gallium oxide, lanthanum oxide, samarium oxide, titanium oxide, zirconium oxide, niobium oxide, and tungsten oxide;
[0052] Optionally, the doping metal source is selected from at least one of zinc oxide, magnesium oxide, aluminum oxide, chromium trioxide, strontium oxide, gallium oxide, lanthanum oxide, samarium oxide, titanium dioxide, zirconium dioxide, niobium pentoxide, and tungsten trioxide;
[0053] The ratio of the total molar amount of nickel and cobalt in the nickel-cobalt hydroxide precursor, the molar amount of aluminum in the aluminum source, and the molar amount of the doping metal in the doping metal source is (0.9-1.3): (0.01-0.03): (0.001-0.003);
[0054] The total molar amount of nickel and cobalt in the nickel-cobalt hydroxide precursor, aluminum in the aluminum source and doped metal in the doped metal source is recorded as c, and the molar amount of lithium in the lithium source is recorded as b, and c:b is (0.95-1.2):1.
[0055] The present invention provides a nickel cobalt aluminum oxide lithium positive electrode material, which is prepared by the above-mentioned nickel cobalt aluminum oxide lithium positive electrode material preparation method.
[0056] The present invention also provides an application of the above-mentioned lithium nickel cobalt aluminum oxide positive electrode material in a lithium ion battery.
[0057] The technical solution of the present invention has the following advantages:
[0058] (1) The preparation method of the nickel cobalt aluminum oxide positive electrode material provided by the present invention comprises the following steps: 1) placing cobalt hydroxide in an acid solution to form an electrolyte, using a graphite rod as an electrode material for electrodeposition treatment, and after the electrodeposition treatment, separating the solid in the electrolyte to obtain a cobalt hydroxide composite material coated with graphene quantum dots; 2) mixing a nickel cobalt hydroxide precursor with a lithium source and an aluminum source, calcining, and obtaining a calcined product; 3) stirring and mixing the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and the calcined product obtained in step 2), and then sintering to obtain the nickel cobalt aluminum oxide positive electrode material. The present invention uses a nickel-cobalt hydroxide binary precursor and then dopes with aluminum to prepare a sintered product instead of directly using a nickel-cobalt-aluminum ternary precursor to prepare a sintered product, which can greatly reduce costs, and can further suppress the lithium-nickel mixed arrangement phenomenon by post-doping with aluminum elements, suppress the phase transition in the charge and discharge process, and improve the cycle stability; at the same time, the present application uses a specific cobalt hydroxide composite material coated with graphene quantum dots and a sintered product for coating and sintering, and the obtained nickel-cobalt-aluminum lithium oxide positive electrode material can isolate the positive electrode material from the contact with the electrolyte to a large extent, reduce the corrosion of the electrolyte, and improve the cycle life of the material; Co in the cobalt hydroxide composite material coated with graphene quantum dots can The DCR is reduced, and the graphene quantum dots have good electron transmission performance, which can be used to reduce the DCR of the positive electrode material and inhibit the growth of the DCR in the cycle process. The two materials are coated together to complement each other to improve the material performance, thereby increasing the first discharge specific capacity and improving the cycle stability. The present invention uses a specific cobalt hydroxide composite material coated with graphene quantum dots and a specifically prepared sintered product for coating and sintering. The obtained nickel cobalt aluminum oxide positive electrode material has the advantages of low DCR, high first discharge specific capacity and high cycle stability, and can also overcome the defects of the prior art nickel cobalt aluminum material that reduces the cobalt content, resulting in increased lithium nickel mixing, reduced interlayer spacing, and hindered lithium ion transmission.
[0059] (2) The preparation method of the nickel cobalt aluminum oxide positive electrode material provided by the present invention, the nickel cobalt hydroxide precursor in step 2) includes a nickel cobalt hydroxide precursor with a first particle size and a nickel cobalt hydroxide precursor with a second particle size; the median particle size D50 of the nickel cobalt hydroxide precursor with the first particle size is 2-4 μm; the median particle size D50 of the nickel cobalt hydroxide precursor with the second particle size is 13-17 μm; the mass ratio of the nickel cobalt hydroxide precursor with the first particle size to the nickel cobalt hydroxide precursor with the second particle size is (1-10): (1-10); the present invention uses two nickel cobalt hydroxide precursors with a large difference in particle size to mix particles, which can improve the grain size, reduce the transmission distance of ion deintercalation, and shorten the ion diffusion time, which will significantly improve the transmission and transfer rate of electrons and ions, and improve the kinetic rate of storage and reaction; thereby further reducing the DCR of the material and improving its cycle performance and first discharge specific capacity.
[0060] (3) The preparation method of the nickel cobalt aluminum lithium positive electrode material provided by the present invention, the step of mixing the nickel cobalt hydroxide precursor with the lithium source and the aluminum source in step 2) also includes the step of adding a doping metal source; optionally, the doping metal source in step 2) is selected from at least one of zinc oxide, magnesium oxide, aluminum oxide, chromium oxide, strontium oxide, gallium oxide, lanthanum oxide, samarium oxide, titanium oxide, zirconium oxide, niobium oxide, and tungsten oxide. The present invention further stabilizes the material structure and reduces the DCR by doping the metal source; for example, by doping zirconium oxide, the material structure can be stabilized, the lithium ion diffusion channel can be stabilized during the charge and discharge process, the grain boundary can be optimized, thereby reducing the material DCR and improving the material cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0062] Figure 1 SEM image of the nickel cobalt aluminum oxide positive electrode material prepared in Example 1 of the present invention;
[0063] Figure 2 Comparison chart of cycle capacity retention rates of button-type batteries corresponding to the nickel cobalt aluminum oxide positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0064] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0065] If the specific experimental steps or conditions are not specified in the embodiments, the conventional experimental steps or conditions described in the literature in the art can be used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional reagent products that can be obtained commercially. Among them, nano cobalt hydroxide and graphite rods can be obtained commercially.
[0066] The particle size of the nano-cobalt hydroxide used in the examples and comparative examples of the present invention is in the range of 100-900 nm.
[0067] Example 1
[0068] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0069] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0070] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0071] 3) 4.731 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0072] Example 2
[0073] This embodiment provides a method for preparing a nickel cobalt aluminum oxide positive electrode material, comprising the following steps:
[0074] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0075] 2) 800g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 200 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0076] 3) 4.731 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0077] Example 3
[0078] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0079] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0080] 2) 600g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 400 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0081] 3) 4.731 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0082] Example 4
[0083] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0084] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0085] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate and 8.338 g of Al2O3 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0086] 3) 4.731 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0087] Example 5
[0088] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0089] 1) Disperse 10g of nano-cobalt hydroxide in 70mL of 15% sulfuric acid aqueous solution and stir evenly, and disperse in an ultrasonic cell disruptor at 400W for 30min. Heat the mixed solution to 65℃ to prepare an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 65℃ with a load current density of 120mA / cm 2 The deposition time is 0.5 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4 ° C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0090] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 500 r / min for 5 min, then at a speed of 1500 r / min for 5 min, and then at a speed of 3000 r / min for 20 min. No waiting time was set in the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 400°C at a heating rate of 3°C / min in an oxygen atmosphere. After calcining at 400°C for 5 hours, the mixed powder was heated to 750°C at a heating rate of 3°C / min, calcined at 750°C for 9 hours, and then calcined at 550°C for 3 hours. The flow rate of the oxygen atmosphere was 3L / min, and then naturally cooled to room temperature. After being crushed and passed through a 45-micron pore size sieve, a calcined product was obtained.
[0091] 3) 5.012 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 800 r / min for 3 min, then at a speed of 1800 r / min for 5 min, and then at a speed of 3200 r / min for 18 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 630° C. at a heating rate of 2° C. / min, sintered for 5 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0092] Example 6
[0093] This embodiment provides a method for preparing a nickel cobalt aluminum oxide positive electrode material, comprising the following steps:
[0094] 1) Disperse 10g of nano-cobalt hydroxide in 100mL of 10% sulfuric acid aqueous solution and stir evenly, and disperse for 120min in an ultrasonic cell disruptor at 200W power, heat the mixed solution to 55°C to prepare an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 55°C, with a load current density of 90mA / cm 2 The deposition time is 0.5 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4 ° C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0095] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1500 r / min for 1 min, then at a speed of 3000 r / min for 1 min, and then at a speed of 4000 r / min for 10 min. No waiting time was set in the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 600°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 600°C for 3 hours, the mixed powder was heated to 700°C at a heating rate of 2°C / min, calcined at 700°C for 12 hours, and then calcined at 450°C for 3 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0096] 3) 4.131 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1200 r / min for 1 min, then at a speed of 2200 r / min for 2 min, and then at a speed of 3600 r / min for 10 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 570°C at a heating rate of 2°C / min, sintered for 7 hours, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0097] Example 7
[0098] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0099] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0100] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0101] 3) 6.3 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0102] Example 8
[0103] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0104] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0105] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0106] 3) 3.15 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0107] Example 9
[0108] This embodiment provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0109] 1) Disperse 10 g of nano-cobalt hydroxide in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse for 60 min in an ultrasonic cell disruptor at 300 W power. Heat the mixed solution to 60 ° C to make an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a cobalt hydroxide composite material uniformly wrapped with graphene quantum dots can be obtained.
[0110] 2) 1000g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set in the variable speed mixing. The large particles of Ni 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0111] 3) 4.731 g of the cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600 ° C at a heating rate of 2 ° C / min and sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0112] Comparative Example 1
[0113] This comparative example provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0114] 1) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0115] 2) 504.731 g of the sintered product obtained in step 2) was stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600° C. at a heating rate of 2° C. / min, sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0116] Comparative Example 2
[0117] This comparative example provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0118] 1) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm 3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0119] 2) 4.731 g of cobalt hydroxide and 500 g of the calcined product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time during the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600° C. at a heating rate of 2° C. / min, sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0120] Comparative Example 3
[0121] This comparative example provides a method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, comprising the following steps:
[0122] 1) Disperse 10 g of lithium aluminate in 100 mL of 12% sulfuric acid aqueous solution and stir evenly, and disperse in an ultrasonic cell disruptor at 300 W for 60 min. Heat the mixture to 60 ° C to prepare an electrolyte, and then insert two graphite rods as positive and negative electrodes for electrodeposition at 60 ° C, with a load current density of 100 mA / cm 2 The deposition time is 1 h, stirring is continued during the process, and the electrolyte is filtered after the electrodeposition is completed. After freeze-drying at -4°C for 3 h, a lithium aluminate composite material uniformly wrapped with graphene quantum dots can be obtained.
[0123] 2) 700g of large Ni particles with a median particle size D50 of 14.58μm 0.90 Co 0.10 (OH)2 precursor (the total molar content of Ni and Co was 10.603 mol / kg after testing), 300 g of small particles of Ni with a median particle size D50 of 2.86 μm 0.90 Co 0.10 The (OH)2 precursor (the total molar content of Ni and Co was 10.624 mol / kg after testing), 452.6 g of lithium hydroxide monohydrate, 8.338 g of Al2O3 and 2.870 g of ZrO2 were mixed in a high-speed mixer at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min. No waiting time was set during the variable speed mixing. The small particles of Ni 0.90 Co 0.10 The specific surface area of the (OH)2 precursor is 7.58 m 2 / g, tap density is 1.90g / cm 3 , large Ni particles 0.90 Co 0.10 The specific surface area of (OH)2 precursor is 9.08m 2 / g, tap density is 2.15g / cm3 After mixing, the mixed powder was placed in a box furnace and heated to 500°C at a heating rate of 2°C / min in an oxygen atmosphere. After calcining at 500°C for 4 hours, the mixed powder was heated to 725°C at a heating rate of 2°C / min, calcined at 725°C for 10 hours, and then calcined at 500°C for 2 hours. The flow rate of the oxygen atmosphere was 2L / min, and then the mixed powder was naturally cooled to room temperature. After being crushed and passed through a 45-micron aperture sieve, a calcined product was obtained.
[0124] 3) 4.731 g of the lithium aluminate composite material coated with graphene quantum dots obtained in step 1) and 500 g of the sintered product obtained in step 2) are stirred and mixed in a high-speed mixer, first at a speed of 1000 r / min for 2 min, then at a speed of 2000 r / min for 3 min, and then at a speed of 3500 r / min for 15 min, without setting a waiting time in the middle of the variable speed mixing, and then placed in a box furnace in an oxygen atmosphere, heated to 600° C. at a heating rate of 2° C. / min, sintered for 6 h, and naturally cooled and sieved to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
[0125] Test Case
[0126] 1. Appearance
[0127] The nickel cobalt aluminum oxide positive electrode material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material presents a granular structure, and the material particles are doped in size and have consistent surface morphology.
[0128] 2. Button battery test
[0129] The nickel cobalt aluminum oxide positive electrode materials prepared in Examples 1-9 and Comparative Examples 1-3 were used as the main materials and the electrical performance tests were carried out according to the following methods. Specifically, the main material, polyvinylidene fluoride and conductive carbon black were weighed in a mass ratio of 95:3:2, and a proper amount of N-methylpyrrolidone was used as a dispersant for homogenization. Then, the aluminum foil was spread flat on a coating machine for coating, and placed in a blast drying oven for drying to remove the dispersant. Then, holes were punched, weighed, and the electrode pieces were baked to obtain positive electrode pieces (surface density 13.3-13.5 mg / cm 2 , compacted density 3.4-3.6mg / cm 2 ); using metallic lithium as the negative electrode, glass fiber as the separator, and 1 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) solution as the electrolyte (the volume ratio of EC to DMC is 1:1), in an argon atmosphere of a glove box, the positive electrode, the negative electrode, the electrolyte, the separator, the gasket and the spring are placed in a button battery shell to assemble a button battery.
[0130] The button cell was subjected to an electrical performance test using a blue electric test system under the conditions of a cut-off voltage of 2.5V-4.25V, and a charge and discharge process of the first cycle (0.2C / 0.2C), the second cycle (0.2C / 1C), the third cycle (0.2C / 1C), and the fourth to the 53rd cycle (1C / 1C). The discharge capacity of the first cycle and the cycle capacity retention rate from the fourth to the 53rd cycle were tested. The test results are shown in Table 1. At the same time, the voltage of 10-second 1C discharge was increased in the 53rd cycle, and the DCR value of the button cell was obtained by voltage / current. The test results are shown in Table 1. The capacity retention rate comparison of the button cell obtained in Example 1 and Comparative Example 1 is shown in Table 1. Figure 2 shown.
[0131] Table 1
[0132]
[0133] As can be seen from the table, from the comparison between Example 1 and Comparative Examples 1-3, it can be seen that the cobalt hydroxide composite material coated with graphene quantum dots has a great improvement in the electrochemical performance of the positive electrode material, which is significantly better than the lithium aluminate composite material coated with cobalt hydroxide alone or coated with specific graphene quantum dots, effectively reducing the DC resistance, and improving the capacity retention rate and the first discharge specific capacity. From Example 1, Example 2, Example 3 and Example 9, it can be seen that the large particle Ni 0.90 Co 0.10 (OH)2 precursor and small Ni particles 0.90 Co 0.10 Different mass ratios of (OH)2 precursors will affect the electrochemical performance of the cathode material. 0.90 Co 0.10 (OH)2 precursor and small Ni particles 0.90 Co 0.10 The best effect was achieved when the mass ratio of (OH)2 precursor was 700:300 (Example 1). 0.90 Co 0.10 (OH)2 precursor (Example 9) has the worst effect. Comparing Example 4 with Example 1, it is found that the doping of zirconium oxide has a significant effect on the improvement of the material. The possible reason is that as the charge and discharge proceed, the lithium ion diffusion channel is stabilized, the grain boundary is optimized, and the DCR of the material is reduced. In addition, a certain amount of doping ions Zr 4+It may also migrate to the electrode surface and form a solid solution, preventing the structural collapse caused by the anisotropic structural change during charge and discharge, and the solid solution also acts as a protective coating to prevent cobalt from dissolving into the electrolyte. Therefore, the material structure becomes very stable during the phase change of the cycle process, and the cycle stability is enhanced. At the same time, the particle size of the material becomes smaller after ZrO2 doping, and the material is easier to deintercalate during the charge and discharge process after the particle size becomes smaller, so the discharge specific capacity of the doped material increases. Comparing Example 1, Example 7 and Example 8, it is found that the positive electrode material (Example 7) prepared when the mass ratio of the cobalt hydroxide composite material coated with graphene quantum dots and a sintered product is 6.3:500 or the positive electrode material (Example 8) prepared when the mass ratio of the cobalt hydroxide composite material coated with graphene quantum dots and a sintered product is 3.15:500, its electrochemical performance is worse than the electrochemical performance of the positive electrode material prepared in Example 1.
[0134] Depend on Figure 2 It can be seen that by comparing the capacity retention rates of the batteries corresponding to the positive electrode materials of Example 1 and Comparative Example 1, the cycle performance of the battery prepared by the positive electrode material using the specific method of the present invention is significantly improved.
[0135] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a nickel cobalt aluminum oxide lithium positive electrode material, characterized in that: The following steps are involved: 1) placing cobalt hydroxide in an acid solution to form an electrolyte, using a graphite rod as an electrode material for electrodeposition treatment, and after the electrodeposition treatment, separating the solid in the electrolyte to obtain a cobalt hydroxide composite material coated with graphene quantum dots; 2) mixing a nickel-cobalt hydroxide precursor with a lithium source and an aluminum source, and calcining the mixture to obtain a calcined product; 3) The cobalt hydroxide composite material coated with graphene quantum dots obtained in step 1) and the sintered product obtained in step 2) are stirred and mixed, and then sintered to obtain the nickel cobalt aluminum oxide lithium positive electrode material.
2. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to claim 1, characterized in that: The cobalt hydroxide described in step 1) is nano cobalt hydroxide; The dosage ratio of the cobalt hydroxide to the acid solution is 1:(5-10), in g:mL; The acid solution is selected from aqueous sulfuric acid, aqueous nitric acid, and aqueous hydrochloric acid; The mass concentration of acid in the acid solution is 10-15%; The current density of the electrodeposition treatment is 90-120 mA / cm 2 The temperature of the electrodeposition treatment is 55-65°C, and the time of the electrodeposition treatment is 0.5-2h.
3. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to claim 1 or 2, characterized in that: In step 2), the ratio of the total molar amount of nickel and cobalt in the nickel-cobalt hydroxide precursor to the molar amount of aluminum in the aluminum source is (0.9-1.3): (0.01-0.03); The total molar amount of nickel element, cobalt element and aluminum element in the nickel cobalt hydroxide precursor is recorded as a, and the molar amount of lithium element in the lithium source is recorded as b, and b:a is (0.95-1.2):1; The lithium source is selected from at least one of lithium carbonate, lithium hydroxide and lithium acetate; The aluminum source is selected from at least one of aluminum oxide and aluminum hydroxide; The chemical formula of the nickel cobalt hydroxide precursor is: Ni x Co y (OH)2, and 0.5≤0x<1, 0 <y≤0.5,x+y=1。 4. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The nickel cobalt hydroxide precursor in step 2) includes a nickel cobalt hydroxide precursor with a first particle size and a nickel cobalt hydroxide precursor with a second particle size; The median particle size D50 of the first particle size nickel cobalt hydroxide precursor is 2-4 μm; The median particle size D50 of the second particle size nickel cobalt hydroxide precursor is 13-17 μm; The mass ratio of the first particle size nickel cobalt hydroxide precursor to the second particle size nickel cobalt hydroxide precursor is (1-10): (1-10); Optionally, the specific surface area of the nickel cobalt hydroxide precursor is 5-10m 2 / g, tap density is 1-3g / cm 3 .
5. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to any one of claims 1 to 4, characterized in that: The mixing in step 2) includes a first stirring and mixing, a second stirring and mixing, and a third stirring and mixing; The first stirring and mixing speed is 500-1500r / min, and the stirring and mixing time is 1-5min; The second stirring and mixing speed is 1500-3000r / min, and the stirring and mixing time is 1-5min; The third stirring and mixing speed is 3000-4000r / min, and the stirring and mixing time is 10-20min; The calcination in step 2) includes heating to 400-600°C for calcination for 3-5h, then heating to 700-750°C for calcination for 9-12h, and then calcining at 450-550°C for 2-5h; The calcining atmosphere includes an oxygen-containing atmosphere; Optionally, the calcination atmosphere includes an air atmosphere or an oxygen atmosphere.
6. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to any one of claims 1 to 5, characterized in that: In step 3), the mass ratio of the cobalt hydroxide composite material coated with graphene quantum dots to the sintered product is (4-5.8):500; The stirring and mixing in step 3) includes: first stirring and mixing at a speed of 800-1200 r / min for 1-3 min, then stirring and mixing at a speed of 1800-2200 r / min for 2-5 min, and then stirring and mixing at a speed of 3200-3600 r / min for 10-18 min.
7. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to claim 6, characterized in that: In step 3), the sintering temperature is 570-630° C. and the sintering time is 5-7 h; The sintering atmosphere includes an oxygen-containing atmosphere; Optionally, the sintering atmosphere includes an air atmosphere or an oxygen atmosphere.
8. The method for preparing the nickel cobalt aluminum oxide positive electrode material according to claim 6 or 7, characterized in that: The step of mixing the nickel cobalt hydroxide precursor with the lithium source and the aluminum source in step 2) further includes the step of adding a doping metal source; Optionally, the doping metal source in step 2) is selected from at least one of zinc oxide, magnesium oxide, aluminum oxide, chromium oxide, strontium oxide, gallium oxide, lanthanum oxide, samarium oxide, titanium oxide, zirconium oxide, niobium oxide, and tungsten oxide; Optionally, the doping metal source is selected from at least one of zinc oxide, magnesium oxide, aluminum oxide, chromium trioxide, strontium oxide, gallium oxide, lanthanum oxide, samarium oxide, titanium dioxide, zirconium dioxide, niobium pentoxide, and tungsten trioxide; The ratio of the total molar amount of nickel and cobalt in the nickel-cobalt hydroxide precursor, the molar amount of aluminum in the aluminum source, and the molar amount of the doping metal in the doping metal source is (0.9-1.3): (0.01-0.03): (0.001-0.003); The total molar amount of nickel and cobalt in the nickel-cobalt hydroxide precursor, aluminum in the aluminum source and doped metal in the doped metal source is recorded as c, and the molar amount of lithium in the lithium source is recorded as b, and c:b is (0.95-1.2):
1.
9. A nickel cobalt aluminum oxide lithium positive electrode material, characterized in that: The nickel cobalt aluminum oxide positive electrode material is prepared by the preparation method of the nickel cobalt aluminum oxide positive electrode material according to any one of claims 1 to 8.
10. Use of the lithium nickel cobalt aluminum oxide positive electrode material according to claim 9 in lithium ion batteries.